On the Stability of Numerical Methods for Nonlinear Volterra Integral Equations. (8th June 2010) - Messina, E.; Muroya, Y.; Russo, E.; Vecchio, A.
Abstract : Here we investigate the behavior of the analytical and numerical solution of a nonlinear second kind Volterra integral equation where the linear part of the kernel has a constant sign and we provide conditions for the boundedness or decay of solutions and approximate solutions obtained by Volterra Runge-Kutta and Direct Quadrature methods.